Towards a Theory of Flavor from Orbifold GUTs - Hall, L; March-Russell, J; Okui, T; Smith, D (2001)
We show that the recently constructed 5-dimensional supersymmetric $S^1/(Z_2× Z_2')$ orbifold GUT models allow an appealing explanation of the observed hierarchical structure of the quark and lepton masses and mixing angles. Flavor hierarchies arise from the geometrical suppression of some couplings when fields propagate in different numbers of dimensions, or on different fixed branes. Restrictions arising from locality in the extra dimension allow interesting texture zeroes to be easily generated. In addition the detailed nature of the SU(5)-breaking orbifold projections lead to simple theories where $b-τ$ unification is maintained but similar disfavored SU(5) relations for the lighter generations are naturally avoided. We find that simple 5d models based on $S^1/(Z_2× Z_2')$ are strikingly successful in explaining many features of the masses and mixing angles of the 2nd and 3rd generation. Successful three generation models of flavor including neutrinos are constructed by generalizing the $S^1/(Z_2× Z'_2)$ model to six dimensions. Large angle neutrino mixing is elegantly accommodated. Novel features of these models include a simple $m_u=0$ configuration leading to a solution of the strong CP problem.